2017
DOI: 10.1007/s00296-017-3892-1
|View full text |Cite
|
Sign up to set email alerts
|

Assistive devices: an effective strategy in non-pharmacological treatment for hand osteoarthritis—randomized clinical trial

Abstract: NCT02667145.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 22 publications
0
18
1
3
Order By: Relevance
“…The WHOQOL‐BREF has been used to evaluate quality of life outcomes in at least one relevant randomized controlled trial. The study investigated the use of assistive devices for hand osteoarthritis compared with the provision of written information .…”
Section: World Health Organization Quality Of Life Short Version Instmentioning
confidence: 99%
“…The WHOQOL‐BREF has been used to evaluate quality of life outcomes in at least one relevant randomized controlled trial. The study investigated the use of assistive devices for hand osteoarthritis compared with the provision of written information .…”
Section: World Health Organization Quality Of Life Short Version Instmentioning
confidence: 99%
“…Thus, while evidence supports combined interventions for thumb OA, we are unable to make specific recommendations regarding combined interventions for knee OA, or for other affected joints. With respect to adjunct interventions, we found evidence to support the use of tape for knee OA 21,55,57 , assistive devices for hand OA 59 , thumb splints for thumb OA 60 , manual therapy for knee OA 23,45,47,53 and neck OA 65 , acupuncture for knee OA 44 , and electrophysical agents for knee OA 19,22,48 (Tables III and IV), while conflicting evidence was found for transcranial direct current stimulation (tDCS) 30,37 (Table IV). Taken together with established clinical guidelines, our findings reinforce that these interventions should be adjuncts to accompany core recommended interventions for OA, rather than be used as standalone or key treatments 2,3,9e16 .…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, studies have been carried out to evaluate the efficacy of AT products, concerning ADL assist devices and upper limb orthoses, in the treatment of patients with OA and RA, obtaining positive results (Clark, 2000;Gomes Carreira et al, 2010;Kjeken et al, 2011;Beasley, 2012;Amaral et al, 2018). The purpose of indicating orthoses and assistive devices for this audience is to minimize wear and maintain joint alignment, prevent deformities, minimize pain, and favor function (Clark, 2000;Beasley, 2012;Almeida et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of indicating orthoses and assistive devices for this audience is to minimize wear and maintain joint alignment, prevent deformities, minimize pain, and favor function (Clark, 2000;Beasley, 2012;Almeida et al, 2015). Based on a clinical trial conducted, Amaral et al (2018) reported that the use of assistive devices improves the occupational performance of individuals with hand osteoarthritis. A recent bibliographic review highlights that the use of orthosis for patients with rheumatoid arthritis provides benefits in skills of manual dexterity, strength gain in grip, and pain relief (Silva & Massa, 2015).…”
Section: Discussionmentioning
confidence: 99%